Integrated Management of Leaf Rot of Coconut - Vrinda T S (Department of Plant Pathology, College of Agriculture, 2002)
The study entitled as "Integrated management of leaf rot of coconut" w as conducted at the Department of Plant Pathology, Co l.cge of Agr iculturc. Ve l l a van i and Iie ld trial was conducted at RARS. Kumarakorn. Extensive iso lai io n s. pathogenicity and characterization studies of the pathogens assoc i aic d with leaf rot infected spindle leaf of coconut from di ffercnt r e g ions 0 I' f ve southern districts of Kerala revealed that Collct otrichu m g/oco.,porioidcs. Fusarium so/ani, Fusarium. monil if..rniae, Fusari utn oxvsp or utn, Cephalosporium sacchari. Exserohilum rostrat um. Gl iocl adi um roselllll.<';C\!o!idillll7 sp. and Curv ular i a sp. played <ignificant roie in t118 ct io lo gj 0" LRD. Based on frequency 01' isolarions. Fusarium spp. .ind C .g/()(;o.,porioides Viere identified as major pathogens or LRD in these areas. The present study constitutes the first report or the ct io log ica l ro l c of Scvt ul uliurn ::;0 in leaf rot incidence. Symptomatology of the disease based on natural incidence in the I'dd